Strategic Thinking's Relationship to Strategic Capabilities: Hubungan Pemikiran Strategis dengan Kemampuan Strategis - Anam Hussain Radi Obaid; Roqaya Kazem ‏ Hamza (Universitas Muhammadiyah Sidoarjo, 2024)
This article examines the application of strategic thinking in the process of organizational strategic management, it comprises the formation and implementation of unique insights and opportunities. It, therefore, creates a competitive advantage for a company or institution. Through key figures to effect positive change for the organization's future, strategic thinking can be accomplished individually or in collaboration. Strategic capabilities are those abilities that distinguish the organization from others to generate and maintain resources, use modern management techniques, and generate technical knowledge to create added value for stakeholders.Strategic thinking is considered its dimensions are (strategic vision, strategic creativity, strategic mind) of dependent variable is strategic capabilities, while its (technological capabilities, administrative capabilities, creative capabilities). It is concluded from the variables that the independent variable is strategic thinking, which has an impact on the dependent variable, which is strategic capabilities. The research sample was represented by a group of individuals working in the Babylon Health Department. The questionnaire was presented to a selected group of (123) employees working in the department. Through several statistical methods, the research reached several results, including that both the independent variable strategic thinking and the dependent variable strategic capabilities are related to each other in a correlation relationship. And that strategic thinking has a direct impact on strategic capabilities Hightlights: Strategic Thinking: Enhances insights, collaboration, and competitive advantage creation. Strategic Capabilities: Focus on resources, management, and knowledge for stakeholder value. Findings: Strategic thinking directly impacts strategic capabilities in organizations. Keywords: Strategic thinking, strategic capabilities